Clearing settlements as instrument of development of economy of Russia (Путеводитель предпринимателя, 2020)
Currently, many banks and nonbankstructures tend to improve the methods, tools, laws and regulations in the field of cash management services entities and non-cash system of payments, for development of the banking market and the economy as a whole. Banks themselves have long been seeking to get away from the concept of indirect cash management services to the settlement services.